PENTINGNYA PENINGKATAN KETRAMPILAN TENAGA KESEHATAN DALAM PREVENTION MOTHER TO CHILD TRANSMITION HIV, SIFILIS, HEP. B PADA IBU HAMIL DI PUSKESMAS KOTA ENDE - owa, khrispina; Wawomeo, Aris; Woge, Yoseph; Sekunda, Maria S. (Kelimutu Nursing Journal, 2023)
HIV, Syphilis and Hepatitis B infections are infectious diseases that are still a health problem in the world, including in Indonesia. The incidence of mother-to-child transmission ranks 5th highest in Asia. HIV transmission from mother to child is 20-45%, Syphilis transmission from mother to child is 69-80% and Hepatitis B transmission from pregnant women to children is 90-95% (Kemenkes RI, 2014). Only 50% of pregnant women are willing to do an examination or test at the initial Antenatal visit while more pregnant women are known to be positive for viral infections in the final trimester which affects the implementation of treatment (Kesga Division of the Ende District Health Office, 2019). The Objectives to analyse the perception of pregnant women about the role of midwives in the success of the PMTCT-HIV, Syphilis, Hepatitis B program for pregnant women at the Ende Regency Health Center. Methods: using a quantitative design method with a correlational analytic approach. The technique for determining respondents used purposive sampling method. The research sample was first trimester pregnant women who checked themselves at the Ende City Health Center from June to August 2021. The sampling technique used the Slovin formula which amounted to 50 respondents. Data were collected from pregnant women's examination cards, MCH books and interviews with respondents. Data processing used the Spearman Rank correlation test with the help of the SPSS for windows 19.00 program. The results of the Spearman Rank variable test of the role of midwives as communicators, motivators, facilitators and counsellors do not have a significant relationship to the success of the PMTCT-HIV, Syphilis, Hepatitis B Program with a value (p-value <0.05), namely 0.656 for the p-value of the role variable as a counsellor, 0.629 for the p-value of the role variable as a motivator, 0.580 p-value for the role variable as a communicator and 0.445 for the p-value of the midwife's role variable as a facilitator. As for the direction of the relationship between the four variables, it has a unidirectional nature according to the positive value of the Corelation Coefficient, and for the level of relationship between the four variables, namely the variable role of midwives as counsellors and motivators has a strong level of relationship (0.656) and (0629), the variable role of midwives as communicators and facilitators has a moderate level of relationship (0.580) and (0.445). Conclusion is necessary to maximize the success of the PMTCT program, including counsellor training for all health workers, especially midwives, the availability of facilities and infrastructure to support activities and counselling efforts in a sustainable, integrated and integrated manner supported by the ability of midwives to manage health programs to improve knowledge and health behaviour in pregnant women.